Evaluation of the effect of core lattice topology on the properties of sandwich panels produced by additive manufacturing. (June 2021) - Monteiro, JG; Sardinha, M; Alves, F; Ribeiro, AR; Reis, L; Deus, AM; Leite, M; Vaz, M Fátima
Sandwich structures are frequently used in automotive, aerospace and marine industries, as they provide adequate functional properties. The two-dimensional regular hexagonal cell shape, i.e. honeycomb is the most used core structure in sandwich panels. Recently, a new type of cellular structures composed of lattice struts has been proposed, as they combine high stiffness, strength and energy absorption with low weight. The main purpose of this research is to investigate the effect of the lattice topology on the flexural behaviour of sandwich panels. Five lattice geometries inspired in crystalline structures were designed, namely, body-centred parallelepiped, body-centred parallelepiped with struts in z -axis, body- and face-centred parallelepiped with struts in z -axis, face-centred parallelepiped with struts in z -axis and parallelepiped simple. The relative density of all the lattices was kept constant as 0.3. Both numerical and experimental approaches were used to evaluate the flexural properties and failure behaviour of the sandwich structures under three-point bending tests. The numerical analysis was undertaken with the finite element software NX Nastran. Taking advantage of additive manufacturing technologies, material extrusion was used to produce polylactic acid samples with the configurations aforementioned. The sandwich panels are composed by a single layer formed by the lattice core and two thin plates, at the bottom and top. The three parts of the panel were manufactured all together. The simulation results indicate that, among the lattices studied, topologies body-centred parallelepiped with struts in z -axis and body- and face-centred parallelepiped with struts in z -axis exhibit higher strength, while body- and face-centred parallelepiped with struts in z -axis shows higher stiffness and higher energy absorption, attaining values that do not differ much from the ones obtained with a two-dimensional hexagonal cellular structure, with the same relative density. As a consequence, some of the geometries studied may have the potential to be considered as alternatives to conventional structures in the design of sandwich structures.